1993
DOI: 10.1017/s0022215100124442
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss in sickle cell anaemia – a United Kingdom study

Abstract: Sensorineural hearing loss (SNHL) has been a well-documented complication of sickle cell disease in the literature from West Africa, West Indies, United States of America and the Middle East. We present a study of 52 patients with homozygous sickle cell disease and 36 control patients with haemoglobin genotype AA, matched for age and sex. Seven patients with sickle cell disease (13.5 per cent) were found to have sensorineural hearing loss i.e.>20 dB at two or more frequencies, while all the patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
1
27
4
Order By: Relevance
“…This finding may suggest that better care may decrease the incidence of SNHL. In this study, we did not find an increase in the frequency of hearing loss with increasing age, a finding which was supported by Friedman et al 2 and Ajulo et al 12 This is in disagreement with others who did find an increased incidence of hearing loss with increasing age. 6 The relationship between SNHL and early occurrence of attacks was suggested by Odetoyinbo and Adekile, who found that more than 90% of those who developed SNHL had their first vaso-occlusive crisis before the age of five years.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…This finding may suggest that better care may decrease the incidence of SNHL. In this study, we did not find an increase in the frequency of hearing loss with increasing age, a finding which was supported by Friedman et al 2 and Ajulo et al 12 This is in disagreement with others who did find an increased incidence of hearing loss with increasing age. 6 The relationship between SNHL and early occurrence of attacks was suggested by Odetoyinbo and Adekile, who found that more than 90% of those who developed SNHL had their first vaso-occlusive crisis before the age of five years.…”
Section: Discussioncontrasting
confidence: 95%
“…2,3,6,7,12,13 Our results of 19% are similar to the previous reports from Saudi Arabia (23.8%), 7 as well as from Nigeria (21.4%) 3 and Jamaica (21.7%). 6 Studies from developed countries revealed much lower frequency of this complication (12% in the US 2 and 13.5% in the UK 12 ). This finding may suggest that better care may decrease the incidence of SNHL.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations